Factors that predict progression-free survival in Chinese lung adenocarcinoma patients treated with epidermal growth factor receptor tyrosine kinase inhibitors - Cui, Shaohua (J Thorac Dis, 2016)
BACKGROUND: Although first-generation epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have shown efficacy in patients with advanced lung cancers, survival predictors with these drugs have not been extensively investigated. This study was performed to explore factors that may predict progression-free survival (PFS) in Chinese lung adenocarcinoma patients treated with EGFR-TKIs. METHODS: We retrospectively collected clinicopathologic data on 208 patients who received either gefitinib, erlotinib or icotinib, including the patients’ EGFR mutation status and levels of six serum tumor markers [carcinoembryonic antigen (CEA), neuron-specific enolase (NSE), cancer antigen 125 (CA125), squamous cell carcinoma antigen (SCC), cytokeratin-19 fragments (CYFRA21-1) and lactate dehydrogenase (LDH)]. Univariate and multivariate survival analyses were performed to identify independent prognostic factors associated with PFS. RESULTS: At the study cutoff date, 189 (90.9%) of the patients met the Response Evaluation Criteria in Solid Tumors (RECIST) version 1.0 criteria for progressive disease (PD), while 19 (9.1%) had stable disease (SD). The median PFS of the 208 patients was 12.4 months (95% CI, 11.0–13.8 months). In the multivariate analysis using a Cox proportional hazard model, a non-smoking history [hazard ratio (HR) =2.460; 95% CI, 1.484–4.079; P<0.001], first-line treatment (HR =1.500; 95% CI, 1.062–2.119; P=0.021), and a high pretreatment serum level of CEA (HR =1.424; 95% CI 1.026–1.977; P=0.035) were found to be significant predictors of a longer PFS. CONCLUSIONS: In Chinese lung adenocarcinoma patients treated with EGFR-TKIs, a non-smoking history, first-line EGFR-TKIs treatment and a high serum level of CEA were independent predictors of a longer PFS along with an EGFR-activating mutation.